(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Urbanization is closely tied to industrialization, modernization, and the social rationalization process. Not only is urbanization a relatively new phenomena, but it is also a historic and rapid shift in human social roots that is taking place all over the world, rapidly displacing rural culture with a more urban one. The outcome of efforts by the public, commercial, and governmental sectors to reduce travel time and cost and enhance housing, job, transit, and educational possibilities is urbanization. The study attempts to comprehend the trends, patterns, and several issues related to urbanization in India using census data from 1901 to 2011. The geographic distribution of urban inhabitants exhibits significant regional variations.Rapid industrialization and rural-to-urban migration caused India's cities' population to grow from 2.58 crore in 1901 to 37.71 crore in 2011. In terms of population density, Goa leads all other Indian states; 62.1% of its residents live in urban areas, according to the 2011 Census of India. With nine cities in 1951, twenty-three in 1991, and fifty in 2011, India has a diverse range of cities nowadays. In essence, this study is descriptive. The data was collected via secondary sources, including books, papers, government records, and internet journals. To assess the effects on society, this research also looks at the complex effects of India's fast urbanization effort.